PEMANFAATAN SISTEM PEMBAYARAN DIGITAL DALAM OPTIMALISASI DIGITAL FUNDRAISING ZAKAT DI MIZAN AMANAH - Lulu Amelia (2022)
Fundraising zakat is the main pillar carried out by zakat management institutions. Along with today's developments, fundraising done on a digital basis. On this basis, zakat collection at amil zakat institutions is carried out by providing digital-based payments. This is a serious concern that must be studied and considered by zakat institutions to provide zakat payment media through digital. The purpose of this study was to find out how the optimization was carried out for fundraising zakat using a digital payment system at the amil zakat institution Mizan Amanah. This study will use a qualitative method with a descriptive analysis approach. This research is a field research with the nature of research in the form of data collection that is compiled, explained, presented, and concluded. The results of this study indicate that Mizan Amanah in utilizing digital payments for digital fundraising , Mizan Amanah provides various digital platforms as zakat portals for muzaki, such as websites, applications, and collaboration with crowdfunding. Mizan Amanah provides many digital payment methods ranging from e-wallet, virtual accounts and credit cardless. In this digital use, although there are several indicators of digital readiness in Mizan Amanah that are not fully fulfilled, in general Mizan Amanah is ready to move digitally to optimize fundraising zakat